2014
DOI: 10.1111/pce.12286
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of phytochrome family in the control of light and gibberellin‐mediated germination in Arabidopsis

Abstract: In several species, seed germination is regulated by light in a way that restricts seedling emergence to the environmental conditions that are likely to be favourable for the success of the new individual, and therefore, this behaviour is recognized to have adaptive value. The phytochromes are one of the most relevant photoreceptors involved in light perception by plants. We explored the redundancy and diversity functions of the phytochrome family in the control of seed responsiveness to light and gibberellins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…Despite its negligible role as an inducer of germination when present alone, phyE acted synergistically with phyC and with phyD to induce germination after exposure to continuous R or to a single pulse of R (Fig 1). Further, phyE acted synergistically with phyB at low R:FR ratios (i.e., during FR treatments), consistent with previous reports [6, 19]. phyC, phyD, and phyE interacted synergistically with phyA under continuous FR, a treatment that specifically activates phyA [18].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Despite its negligible role as an inducer of germination when present alone, phyE acted synergistically with phyC and with phyD to induce germination after exposure to continuous R or to a single pulse of R (Fig 1). Further, phyE acted synergistically with phyB at low R:FR ratios (i.e., during FR treatments), consistent with previous reports [6, 19]. phyC, phyD, and phyE interacted synergistically with phyA under continuous FR, a treatment that specifically activates phyA [18].…”
Section: Resultssupporting
confidence: 89%
“…phyB and phyA have emerged as the most important phytochromes [1, 2, 18, 29], whereas the roles of phyD, phyE, and phyC have been assumed to be minor and redundant with phyB [6, 11, 12, 14, 15, 22, 24, 40, 41]. However, our knowledge about the capacity of individual phytochromes to elicit specific responses and the interactions among them is still incomplete.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significance of individual phytochromes in seed germination was first established in a comparative analysis of mutants deficient in PhyA, PhyB, and PhyA/PhyB in Arabidopsis. These studies indicated that PhyB is an important regulator of seed germination in red light via the low fluence response (LFR) mode, while PhyA mediates very low fluence responses (VLFR) in red and far-red light (Shinkle and Briggs, 1984;Footitt et al, 2013;Arana et al, 2014). Heschel et al (2007) demonstrated that temperature-responsive phytochrome-mediated germination pathways affect seed germination, with PhyA and PhyE promoting seed germination at warmer and colder temperatures, respectively, and PhyB promoting seed germination across a range of temperatures.…”
Section: Phytochrome Signaling In Arabidopsismentioning
confidence: 97%